IMPLEMENTASI PROGRAM JAMINAN KESEHATAN MASYARAKAT (JAMKESMAS) DI PUSKESMAS GEYER I KECAMATAN GEYER KABUPATEN GROBOGAN - Agung Probo Muljono (JI@P, 2015)
Agung Probo, 2015. “implementation of Community Health Insurane(JAMKESMAS) at the Community Health Center (PUSKESMAS) in Geyer,Grogogan Regence”. Slamet Riyadi University, Thesis, unpublished.PUSKESMAS as the first-order healthcare service is expected to provide aholistic, comprehensive, and sustainable service. When patient needsintermediate service, he/she should be referred to second-order healthcareservice provider. Puskesmas provides healthcare service to general society,either JAMKESMAS member or non-JAMKESMAS member patients.PUSKESMAS plays an important part in the implementation of JAMKESMASservice because in PUSKESMAS, the patient can obtain health servise freely.The objective if research was to find out the implementation of JAMKESMASProgram in PUSKESMAS Geyer of Grobogan Regency in the attempt ofsatisfying the basic need for the poor and for the disadvantaged communitymember. This study was a qualitative research taken place in PUSKESMAS IGeyer Grobogan Regency. The sampling technique employed was purposivesampling. The types of data were primary and secondary data. Techniques ofcollecting data were interview, documentation and observation. Technique ofdata analysis used was an interactive model analysis. The result of researchindicated that the implementation of JAMKESMAS Program in PUSKESMAS IGeyer Grobogan Regency had run well. It could be seen from theimplementation of Edward III’s policy implementation model has been alreadyconsisted of communication, resource, attitude disposition, and bureaucracystructure. The internal communication had run well but the external one stillneeded to be improved. The human resource had been able to implement theJAMKESMAS Program policy well. The facility existing in PUSKESMAS hadbeen sufficiently complete and for certain cases, the PUSKESMAS referred thepatients to hospital. The employees had commitment and honesty in helpingimplement the JAMKESMAS program. Bureaucracy structure had beenconsistent with respective duties. The work atmosphere also supported theimplementation of JAMKESMAS Program and the cooperation among thoseinvolved in Puskesmas had also run well.Keywords: policy implementation, communication, resource, attitude disposition,bureaucracy structure.